Lista de répteis do Brasil: atualização de 2022 - Guedes, Thaís B.; Entiauspe Neto, Omar M.; Costa, Henrique C. (Herpetologia Brasileira, 2026)
We present the updated Brazilian list of reptiles for the year 2022. Brazil has 856 species of reptiles recorded within its borders: 39 Testudines, 6 Crocodylia, and 811 Squamata (81 amphisbaenians, 295 lizards, and 435 snakes). If subspecies are counted, the number increases to 889 taxa. Brazil supports the third richest reptile fauna in the world. A total of 404 species (47.2%) of Brazilian reptiles are endemic to the country, mainly amphisbaenians (79%), followed by lizards (55.5%), snakes (38.6%), and chelonians (20.5%). During the past year, 21 federative units had an increase in the number of species, three showed decrease and the remaining three maintained the same diversity as in the previous year’s List of Reptiles. Mato Grosso, Bahia, and Pará are the richest federative units in number of species and species+subspecies. Bahia, Minas Gerais, and São Paulo support the most Brazilian endemic species. We also comment on nomenclatural changes, species and subspecies included or excluded for the country, and for each federative unit since the previous checklist.